IMPLEMENTASI PEMBELAJARAN PAI SESUAI KURIKULUM COVID PADA MTSN 2 KEPULAUAN SULA - Ibrahim Umasugi (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
This study discusses the implementation of Islamic Religious Education (PAI) learning adapted to the Covid-19 emergency curriculum at MTsN 2 Sula Islands. The curriculum has an important role in the educational process, and this study aims to examine the implementation of PAI learning according to the curriculum adapted to the Covid-19 pandemic situation. In this study, interviews were conducted with school principals, vice principals for curriculum, and teachers as data sources. The results of the analysis show that the supporting and inhibiting factors that influence the implementation of the Covid-19 emergency curriculum include teacher readiness, financial problems, the role of parents in supervising online learning, and internet network limitations. In its implementation, there are four important things, namely developing teacher competence, changing learning patterns, using technology, and measuring results. This research is expected to contribute to the development of effective and adaptive PAI learning methods and strategies in the midst of an ongoing pandemic situation